Kajian Terhadap Asas-Asas Teologis Dalam Surah An-Nisa’ Ayat 129 Tentang Aturan Konkrit Monogami - Hafis, Muhammad (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2023)
Man is naturally a social being who can’t live alone. The Marriage Association is a legitimate link between a man and a woman for a long time. Therefore, people always live with each other. The family is the smallest social group of a society, which is expected to maintain the continuity of human life in the world. Monogamy is marriage with only one wife. This sentence comes from the Greek monos which means One and gamos Married. Monogamy is a marriage between a man and a woman. Monogamy is the principle of marriage in Islam, so that a husband may marry more than one wife as long as he does fair (wise), while fair is a difficult thing to uphold, Allah decreed, if you cannot do justice, then it is sufficient to marry a woman.